Contracting in a supply chain - Lariviere, Martin A. (Henry Stewart Talks, 2012)
Contracting under demand uncertainty, Consequence of misaligned incentives, Partial returns policies, Properties of coordinating contracts, When to implement advanced contracts, Additional complications